Fecal and Circulating TNF-a Measurement for Assessment of Disease Activity in Inflammatory Bowel Disease - Ahmet DOBRUCALI; Murat TUNCER; Yeşim TUNCALI ERALP; Kadir BAL; İbrahim YURDAKUL and Mehmet ALTIN and İsmail DİNÇ and Fatma AŞCIOGLU (Turkish Journal of Gastroenterology, 2020)
-